Toxic infestation by bee sting in dog - Silva Sousa, Jéssica (Pubvet, 2018)
Accidents due to bee stings in dogs occur frequently, however, there are few cases described in the literature. This report describes a fatal case of a canine, with signs of systemic toxic reaction due to a bees accident. The main clinical signs were hemolysis and hemoglobinuria. Other findings included tachycardia, and dyspnoea as well as the presence of stings in the animal's body. Despite the institution of clinical treatment, the animal died two hours later.
Keywords: bee; anaphylaxis; hemolytic anemia; dog; emergency